Utilization of Educational Games For Distance Learning In Mathematics Class VIII Middle School - Nur Kholifah, Anisa; Masitoh, Siti; Yolanita Maureen, Irena (Green Publisher Indonesia, 2022)
The development of information and communication technology has now touched various domains that are able to change conventional methods into modern ones. As an example of technological developments in student learning media which are now varied and creative, such as the application of learning through educational-themed games. The game contains content in the form of interesting and interactive learning materials with the aim of being able to increase student interest in learning and form a fun learning environment. This study used the research and development (R&D) method with the aim of implementing a design game with the theme of educating mathematics subjects at the VIII grade level of junior high school in the distance learning process. The results of the study, namely educational game learning media, met the validity criteria with an average proportion obtained from expert validators of 85.94% and included in the